Subnational inequalities and preventable gaps in drowning premature mortality and non-fatal health loss among population younger than 20 years - Gengfeng Su; You Zeng; Wenyi Jin; Queran Lin; Shihao Wang; Pi Guo; Junyan Xi; Lian Liang; Jiajia Wang; Bingying Fan; Min Huang; Jingxuan Jia; et al. (Frontiers in Public Health, 2026)
Background Drowning remains a preventable cause of premature mortality among children and adolescents. National estimates can monitor progress, but may not identify subnational locations where risk remains high. We examined drowning burden in the population younger than 20 years in 2023, focusing on age patterns, national differences, subnational variation, and frontier gaps. Methods We analyzed 1990–2023 population health estimates for drowning. Deaths, disability-adjusted life-years (DALYs), death rates, and DALY rates were summarized globally and across 204 countries and territories. Subnational DALY-rate analyses included 507 locations in 17 countries. We assessed age-specific patterns, rankings by DALY rate and the number of DALYs, subnational variation, sociodemographic inequality, and frontier gaps. Subnational frontier analyses included 389 locations in 14 countries with available estimates on socio-demographic index and DALY rates. Results In 2023, drowning caused 127,762 deaths and 10.48 million DALYs in the population < 20 years. Death and DALY rates declined by 68.4% and 68.8% from 1990 to 2023, while years of life lost accounted for 99.86% of DALYs. The highest DALY rate occurred at ages 12–23 months. Rankings by DALY rate and by the number of DALYs identified different national and subnational priorities. Subnational analyses showed large within-country variation. At the national level, positive frontier gaps were observed in 199 of 204 countries and territories. Among subnational locations with available frontier inputs, positive gaps were observed in 374 of 389 locations across 14 countries. Conclusion Drowning in the population < 20 years still caused substantial premature mortality in 2023. Age patterns, rate-based and number-based rankings, subnational variation, and frontier gaps showed that national averages alone were insufficient to identify all priority populations for drowning prevention.